THE FEATURES AND THE PLACE OF CHANGE MANAGEMENT IN THE GENERAL MANAGEMENT SYSTEM IN AN ENTERPRISE - KLYMCHUK, Alona; LEVYTSKA, Inna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The extremely high turbulence of the international economic and socio-political environment in recent years has made it necessary to revise the prevailing concepts and models of successful change management in enterprises in order to adapt them to new economic realities and challenges. At the same time, the wider the range of modern research on this issue becomes, the more discrepancies and inaccuracies in the formation of the theoretical basis for effective change management begin to fill the scientific discourse, making it difficult for both theorists and real managers to work on the implementation of appropriate management systems, their improvement and adaptation to existing and future challenges and needs. That is why the issues of specifying the peculiarities of change management and its place in the overall management system are of particular relevance today. Theoretical substantiation of the features and place of change management in the overall management system of an enterprise based on a critical analysis of existing approaches. The methodological basis of the study was formed by general scientific and special methods of economic theory, and, in particular, methods of theoretical generalization and comparative analysis, designed to facilitate a comprehensive consideration of the issue under study. Thus, in the course of the study, the author critically analyzed the modern English-language and Ukrainian-language scientific discourses on the above-mentioned issues, substantiated key inaccuracies and identified ways to eliminate them based on the proposed sequence of substantiation of the features and place of change management in the overall management system of an enterprise. The peculiarities of the interpretation of the term “change management” in the English and Ukrainian scientific discourses are studied. A critical analysis of these interpretations is carried out in the context of distinguishing between the essential aspects of change management and enterprise management in general. The approaches to identifying changes that require a special management technology are studied and basic ways to determine the range of such changes in an enterprise are proposed. On the basis of a consistent substantiation of the features and place of change management in the overall management system of an enterprise, the functions of the overall management system of an enterprise and change management as its component are differentiated.